FORMULATON AND EVALUATION OF SOLID LIPID NANOPARTICLES CONTAINING DOXORUBICIN AND CURCUMIN-PREFORMULATION STUDIES AND ACTIVITY - Rahul Singh,Vikrant Verma, Aadesh Kumar, Nidhi Dhama (Chelonian Research Foundation, 2024)
Many controlled delivery strategies have been developed in recent years in an effort to increase the solubility, stability, and bioavailability of medications that are poorly absorbed. Lipid nanoparticles have particularly intriguing qualities when it comes to delivering drugs or genes. These systems, made up of lipids stabilized with surfactants. A flexible drug delivery method called solid lipid nanoparticles (SLNs) has been formulated with homogenization process and formulation was optimized .This work aimed to synthesize solid lipid nanoparticles containing curcumin and doxorubicin. Results were found satisfactory from the preformulation examination consisting of solubility studies, particle size and LOD with no incompatibility issues with the excipients. Entrapment of both drugs in SLNs have increased the pharmacological activity compare to that available in crude drug form. In-vitro release kinetics shows sustained release with initial burst effect. The linearity was established in the concentration of 0.2- 10μg/ml for curcumin and 0.015 - 62.50µg/mL for doxurubicin. Keywords: Chemotheraphy, Chromatogram,Solid lipid Nanoparticles,Doxorubicin, Anticancer agent, Curcumin